Information Technology, Organizational Form, and Transition to the Market - John S. Earle; Ugo Pagano; Maria Lesi (W.E. Upjohn Institute for Employment Research, 2002)
The paper reviews theories of information technology adoption and organizational form and applies them to an empirical analysis of firm choices and characteristics in four transition economies: the Czech Republic, Hungary, Romania, and Slovakia. We argue that these economies have gone through two major structural changes-one concerning new technology and another concerning ownership and boundaries of firms-and we consider if and how each one of the two structural changes has affected the other. We test the impact of firm size, integration, and ownership on the extent of new information technology adoption (measured by growth in the fraction of employees using personal computers or computer-controlled machinery), and the impact of information technology on changes in the boundaries and the ownership structure of enterprises, drawing upon a sample survey of 330 firms.
Keywords: P1; P5; L2; O3; 330; transition; economy; Earle; technology; organizational; form; Pagano; Lesi